THE EFFECT OF PRICE, QUALITY OF PRODUCT AND QUALITY OF SERVICE TO PURCHASE INTEREST IN SEA TRANSPORTATION SERVICE AT PT. MARINATAMA GEMANUSA BATAM ROUTE TELAGA PUNGGUR - TG. PINANG. - Riky Aprianto; Lukmanul Hakim (Universitas Riau Kepulauan, 2016)
This thesis titled